Alberta’s Oil Sands Reclamation Policy Trajectory: The Role of Tense Layering, Policy Stretching and Policy Patching in Long-Term Policy Dynamics - Adam Wellstead (Taylor & Francis, 2018)
10.1080/09640568.2015.1098594